A continuum theoretical model and finite elements simulation of bacterial flagellar filament phase transition. (3rd October 2017) - Wang, Xiaoling; Meng, Shuo; Han, Jingshi
Abstract: The Bacterial flagellar filament can undergo a polymorphic phase transition in response to both mechanical and chemical variations in vitro and in vivo environments. Under mechanical stimuli, such as viscous flow or forces induced by motor rotation, the filament changes its phase from left-handed normal (N) to right-handed semi-coiled (SC) via phase nucleation and growth. Our detailed mechanical analysis of existing experiments shows that both torque and bending moment contribute to the filament phase transition. In this paper, we establish a non-convex and non-local continuum model based on the Ginzburg-Landau theory to describe main characteristics of the filament phase transition such as new-phase nucleation, growth, propagation and the merging of neighboring interfaces. The finite element method (FEM) is adopted to simulate the phase transition under a displacement-controlled loading condition (rotation angle and bending deflection). We show that new-phase nucleation corresponds to the maximum torque and bending moment at the stuck end of the filament. The hysteresis loop in the loading and unloading curves indicates energy dissipation. When the new phase grows and propagates, torque and bending moment remain static. We also find that there is a drop in load when the two interfaces merge, indicating a concomitant reduction in the interfacial energy. Finally, the interface thickness is governed by the coefficients of the gradient of order parameters in the non-local interface energy. Our continuum theory and the finite element method provide a method to study the mechanical behavior of such biomaterials.